2007
DOI: 10.4049/jimmunol.178.1.111
|View full text |Cite
|
Sign up to set email alerts
|

Spleen Tyrosine Kinase (Syk), a Novel Target of Curcumin, Is Required for B Lymphoma Growth

Abstract: Curcumin (diferuloylmethane), a component of dietary spice turmeric (Curcuma longa), has been shown in recent studies to have therapeutic potential in the treatment of cancer, diabetes, arthritis, and osteoporosis. We investigated the ability of curcumin to modulate the growth of B lymphomas. Curcumin inhibited the growth of both murine and human B lymphoma in vitro and murine B lymphoma in vivo. We also demonstrate that curcumin-mediated growth inhibition of B lymphoma is through inhibition of the survival ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(44 citation statements)
references
References 64 publications
2
41
0
1
Order By: Relevance
“…[38][39][40] Our data are consistent with studies performed with DLBCL cell lines, which showed that the inhibition of Syk with the inhibitor curcumin or the downregulation of Syk by RNA interference reduces basal Akt phosphorylation. 31 It should be noted, however, that in unstimulated CLL cells the levels of phosphorylated Akt and ERK are relatively low, especially in comparison with CLL cells stimulated through the BCR. .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[38][39][40] Our data are consistent with studies performed with DLBCL cell lines, which showed that the inhibition of Syk with the inhibitor curcumin or the downregulation of Syk by RNA interference reduces basal Akt phosphorylation. 31 It should be noted, however, that in unstimulated CLL cells the levels of phosphorylated Akt and ERK are relatively low, especially in comparison with CLL cells stimulated through the BCR. .…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29][30] Inhibition or downregulation of Syk in DLBCL and follicular lymphoma cell lines resulted in decreased phosphorylation of downstream signaling molecules and inhibition of proliferation and survival, indicating that constitutively active Syk contributes to the growth of these malignancies. 26,27,30,31 In addition, translocations involving Syk have recently been identified in patients with myelodysplastic syndrome and peripheral T-cell lymphoma, further suggesting that this kinase may function as a proto-oncogene. These translocations generate fusion proteins in which the tyrosine kinase domain of Syk is joined to the dimerization domain of the transcription factor TEL or to the N-terminal pleckstrin homology domain of the inducible T cell kinase.…”
Section: Introductionmentioning
confidence: 99%
“…As predicted by the spectrum of its TK inhibitory activity, imatinib also induces dramatic clinical and molecular responses in CMML patients with dysregulated PDGFRb (Apperley et al, 2002) and in CEL patients with PDGFRa fusions (Klion et al, 2003). The non-receptor SH2-containing TK Syk is fused to TEL in some patients with myelodysplastic syndrome, and small molecule Syk kinase inhibitors impair proliferation and survival of some precursor B-lymphoid leukemias and lymphomas (Wossning et al, 2006;Gururajan et al, 2007). Several inhibitors of FLT3 kinase activity in clinical development can inhibit growth and induce apoptosis in hematopoietic cell lines expressing activated FLT3, and have therapeutic efficacy in murine models of FLT3-induced leukemia (Weisberg et al, 2002).…”
Section: Pathogenic and Therapeutic Implications Of Dysregulated Tk Smentioning
confidence: 99%
“…Recently, a t(5;9)(q33;q22) translocation 2 was reported in a subgroup of PTCL with follicular involvement, 3 resulting in overexpression of the SYK gene under the control of the ITK promoter. SYK encodes a cytoplasmic PTK, which is important in proliferation and prosurvival signaling [4][5][6][7] and is expressed in a variety of hematopoietic cells, including normal B lymphocytes 8 and most B-cell lymphomas. 5,[9][10][11][12] Normal peripheral T cells, however, generally lack Syk protein expression.…”
Section: Introductionmentioning
confidence: 99%